Harnessing genetic resources and progress in plant genomics for fonio (Digitaria spp.) improvement - Ayenan, M.A.T.; Sodedji, K.A.F.; Nwankwo, C.I.; Olodo, K.F.; Alladassi, M.E.B. (Genetic Resources and Crop Evolution, 2018)
Fonio plays an important role in food security and in income generation, in drought prone areas of West Africa. This review aimed at highlighting fonio production constraints, breeding objectives and available genetic resources for fonio improvement. Lack of institutional support to research, lack of improved seeds, parasitic weed infestation, grain shattering, lodging and toilsome of the post-harvest handling are the major constraints limiting fonio production. These factors lead to negligence of the crop notwithstanding its high nutritional and market values. Breeding programs on fonio should first focus on solving these problems to improve overall yield. We explored the potential of mutation breeding, somaclonal variation, somatic hybridization, molecular markers, comparative genomics, individualized targeting induced local lesions in genomes (iTILLING), genotype by sequencing and genomic selection to develop improved fonio varieties. Determination of ploidy level, wide collection and characterization of fonio genetic resources, definition of core reference set collection, and exploitation of heterosis are some key research areas that would be of great interest in fonio improvement. However, this can only be achieved with adequate funding and institutional support.
Keywords: Breeding; Digitaria spp; Genetic resources; Genomics; Gramineae; Neglected and underutilized crop